2016
DOI: 10.1186/s12886-016-0385-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser trabeculoplasty for early glaucoma: analysis of success predictors and adjusted laser outcomes based on the untreated fellow eye

Abstract: BackgroundTo identify success predictors and to study the role of the fellow untreated eye as a co-variable for adjustment of intraocular pressure (IOP) outcomes following selective laser trabeculoplasty (SLT) in early open-angle glaucoma (OAG) patients.MethodsA case series was carried out. Patients with uncontrolled early OAG or ocular hypertension (inadequate IOP control requiring additional treatment) underwent SLT (one single laser session) performed by the same surgeon in a standardized fashion. The same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Many studies have attempted to characterize potential predictive factors of success following SLT and we sought to assess current claims and to contribute currently unexplored predictive factors such as total energy delivery during treatment. Our results agree with the frequently reported finding that baseline IOP is a predictor of SLT success [16][17][18][19][20][21][22] , while factors such as patient age, PTM, and type of glaucoma are not 17,[20][21][22][23][24] . Some of the literature reports an association between heavily pigmented PTM and IOP spikes but we did not observe this in our population 9,24 .…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have attempted to characterize potential predictive factors of success following SLT and we sought to assess current claims and to contribute currently unexplored predictive factors such as total energy delivery during treatment. Our results agree with the frequently reported finding that baseline IOP is a predictor of SLT success [16][17][18][19][20][21][22] , while factors such as patient age, PTM, and type of glaucoma are not 17,[20][21][22][23][24] . Some of the literature reports an association between heavily pigmented PTM and IOP spikes but we did not observe this in our population 9,24 .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the results of the subanalysis by baseline IOP levels in this subgroup of treatment-naïve patients confirmed that the greatest response to the preservative-free tafluprost/timolol fixed combination is obtained in patients with higher baseline IOP levels. This finding is consistent with the results of a meta-analysis of double-masked, controlled phase III studies with fixed combination products of prostaglandin and timolol published by Holló et al20 and for other treatment options like selective laser trabeculoplasty 21,22. In the study of Holló a similar reduction in IOP of ~32%–36% from untreated baseline IOP levels between 24 and 29 mmHg was reported 20.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is consistent with the results of a meta-analysis of double-masked, controlled phase III studies with fixed combination products of prostaglandin and timolol published by Holló et al 20 and for other treatment options like selective laser trabeculoplasty. 21 , 22 In the study of Holló a similar reduction in IOP of ~32%–36% from untreated baseline IOP levels between 24 and 29 mmHg was reported. 20 Furthermore, this meta-analysis revealed that IOP reductions of up to 40% and beyond could be achieved for untreated baseline pressures of 31 mmHg or higher.…”
Section: Discussionmentioning
confidence: 57%
“…Our results indicated that age, sex and exfoliation were not predictors of survival of treatment, in agreement with previous studies that also studied other variables. Ethnicity, type of glaucoma, family history of glaucoma, history of previous ALT, myopia, systemic disease (e.g., high blood pressure and DM), simultaneous eye drops (e.g., prostaglandins), visual function, pigmentation of TM, angle grade, phakic/pseudophakic state of lens and central corneal thickness were not found to be significant predictors either (Martow et al 2011;Leahy & White 2015;Chun et al 2016).…”
Section: Discussionmentioning
confidence: 90%